Lithospheric structure of Venus from gravity and topography - Jimenez-Diaz, A.; Ruiz, J.; Kirby, Jon; Romeo, I.; Tejero, R.; Capote, R. (Academic Press, 2015)
There are many fundamental and unanswered questions on the structure and evolution of the Venusian lithosphere, which are key issues for understanding Venus in the context of the origin and evolution of the terrestrial planets. Here we investigate the lithospheric structure of Venus by calculating its crustal and effective elastic thicknesses (Tc and Te, respectively) from an analysis of gravity and topography, in order to improve our knowledge of the large scale and long-term mechanical behaviour of its lithosphere. We find that the Venusian crust is usually 20-25 km thick with thicker crust under the highlands. Our effective elastic thickness values range between 14 km (corresponding to the minimum resolvable Te value) and 94 km, but are dominated by low to moderate values. Te variations deduced from our model could represent regional variations in the cooling history of the lithosphere and/or mantle processes with limited surface manifestation. The crustal plateaus are near-isostatically compensated, consistent with a thin elastic lithosphere, showing a thickened crust beneath them, whereas the lowlands exhibit higher Te values, maybe indicating a cooler lithosphere than that when the Venusian highlands were emplaced. The large volcanic rises show a complex signature, with a broad range of Te and internal load fraction (F) values. Finally, our results also reveal a significant contribution of the upper mantle to the strength of the lithosphere in many regions.